Agriculture and undernutrition through the lens of economics - Headey, Derek D.; Masters, William A. (International Food Policy Research Institute, 2019)
Agricultural development has historically focused on poverty reduction and food security but is now increasingly asked to help improve nutrition. Despite this strengthened nutritional mandate, agricultural policies and programs have struggled to develop effective, scalable and cost-effective approaches for reducing undernutrition. This study was therefore undertaken to assess more the more strategic issue of how to re-design agricultural development strategies for greater nutritional impact. To do so we review the literature on agriculture-nutrition linkages through an economic lens, focusing on systemic agriculture-nutrition linkages that go beyond the much-explored question of how a farm family’s agricultural activities affect their own household members’ food consumption or nutrition outcomes. To that end we structured this review around three types of linkages between agriculture and nutrition: (i) agricultural income effects (including income stability); (ii) relative food price determination (including the shadow prices involved in consuming one’s own production); and (iii) agricultural livelihood characteristics (encompassing the many neglected dimensions of agricultural activities and rural livelihoods that influence nutrition and health). For each of these literatures we reflect upon relevant economic theory, methodological challenges, and key empirical evidence. We conclude with a brief discussion of the implications of these findings for developing more nutrition-sensitive agricultural development strategies.